(untitled) (Ustozlar uchun, 2026)
In today’s globalized world, the ability to communicate effectively across cultural boundaries has become an essential skill. Foreign language education is no longer limited to mastering grammar and vocabulary; it increasingly encompasses the development of intercultural communication competence (ICC). ICC refers to the ability to interact appropriately and effectively with individuals from diverse cultural backgrounds. This competence enables language learners to navigate cultural nuances, avoid misunderstandings, and engage in meaningful communication in real-life contexts.